Analisis Pengaruh Komite Audit Free Cash Flow dan Leverage terhadap Manajemen Laba pada Perusahaan Manufaktur di Bursa Efek Indonesia - Nursanty, Ida Ayu; Kartini, Endang; Prathama, Baiq Destania; Octavia, Yusi Faizathul (Valid: Jurnal Ilmiah, 2024)
This research aims to analyze the influence of audit committee, free cash flow and leverage on earnings management in manufacturing companies in the metal sector and the like on the Indonesia Stock Exchange in 2019-2022. This research variable consists of 3 (three) independent variables, namely audit committee (X1), free cash flow (X2), and leverage (X3) and the dependent variable is earnings management (Y). The type of research used in this research is associative. The population in this study amounted to 17 companies. The sampling technique in this research used the Purposive Sampling method. The samples used in this research were 11 samples. The data analysis technique used in this research is multiple linear regression. Based on the research results, it shows that the audit committee variable, free cash flow, has no effect on earnings management, while leverage has an effect on earnings management.